2016
DOI: 10.1080/19420862.2016.1143182
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD73 AMP hydrolysis by a therapeutic antibody with a dual, non-competitive mechanism of action

Abstract: M. Damschroder (2016) Inhibition of CD73 AMP hydrolysis by a therapeutic antibody with a dual, non-competitive mechanism of action, mAbs, 8:3, 454-467, DOI: 10.1080/19420862.2016 ABSTRACT CD73 (ecto-5 0 -nucleotidase) has recently been established as a promising immuno-oncology target. Given its role in activating purinergic signaling pathways to elicit immune suppression, antagonizing CD73 (i.e., releasing the brake) offers a complimentary pathway to inducing anti-tumor immune responses. Here, we describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 55 publications
8
75
0
Order By: Relevance
“…Suppression of syngeneic tumors included the activation of immune-activating cytokines IFNg and TNF-a, among others. 13,14 MEDI9447 was developed to minimize Fc-receptor (FcR) engagement; however, a recent study by Young et al identified that the anti-metastatic activities of anti-CD73 mAb were largely reliant on the ability of the mAb to engage Fc receptor, in particular, FcgRIV on CD11b C Gr-1 C myeloid cells. 11 Similar studies in the past have been instrumental in deciphering the mechanism underlying the clinical activities of anti-CTLA-4, 15,16 and anti-HER2 17 mAbs.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of syngeneic tumors included the activation of immune-activating cytokines IFNg and TNF-a, among others. 13,14 MEDI9447 was developed to minimize Fc-receptor (FcR) engagement; however, a recent study by Young et al identified that the anti-metastatic activities of anti-CD73 mAb were largely reliant on the ability of the mAb to engage Fc receptor, in particular, FcgRIV on CD11b C Gr-1 C myeloid cells. 11 Similar studies in the past have been instrumental in deciphering the mechanism underlying the clinical activities of anti-CTLA-4, 15,16 and anti-HER2 17 mAbs.…”
Section: Introductionmentioning
confidence: 99%
“…This antibody hinders the conversion of both membrane-bound and soluble CD73 from the inactive open conformer to the catalytically active close state, through the interaction with a binding site within the CD73 N-terminal domain. 6 The authors reported that the mechanism of action of MEDI9447 is therapeutically advantageous, since the lack of competition with the AMP binding site on CD73 makes it unlikely to have potential cross-reactions with other nucleotide/side binding proteins endowed with structurally conserved catalytic sites. 6 In addition, the efficacy of MEDI9447 in inhibiting CD73 does not require the blockade of multiple substrates at level of the active site.…”
mentioning
confidence: 99%
“…6 The authors reported that the mechanism of action of MEDI9447 is therapeutically advantageous, since the lack of competition with the AMP binding site on CD73 makes it unlikely to have potential cross-reactions with other nucleotide/side binding proteins endowed with structurally conserved catalytic sites. 6 In addition, the efficacy of MEDI9447 in inhibiting CD73 does not require the blockade of multiple substrates at level of the active site. 6 The study by Hay et al, 7 published in the present issue of OncoImmunology, points out the wide-ranging role of CD73-derived adenosine on the phenotype of both lymphoid and myeloid-derived cells, shaping both the innate and adaptive arms of antitumor immunity.…”
mentioning
confidence: 99%
See 2 more Smart Citations